Effects of bracings and motion coupling on resonance features of semi-submersible platform under irregular wave conditions. (January 2020) - Wei, Handi; Xiao, Longfei; Low, Ying Min; Tian, Xinliang; Liu, Mingyue
Abstract: Resonance is a critical consideration in the design of offshore floating structures. This paper aims at analysing the nonlinear effects of bracings and motion coupling on the resonance features of a semi-submersible platform. An improved mathematical model based on potential theory is proposed to simulate the motion response of a semi-submersible platform under irregular wave conditions, considering both the variations of hydrostatic and hydrodynamic forces induced by the bracings entering and exiting the water and the nonlinear coupling induced by the platform motions. For comparison purposes, numerical simulations are also performed using a mathematical model without considering the aforementioned effects. Validated by results of wave basin tests and numerical simulations, the proposed model performs much better in capturing the characteristic resonance features of pitch motion in low-frequency region. The nonlinear hydrostatic effect of bracings leads to the increase of resonance frequency as the motion amplitude increases, while the hydrodynamic force on the bracings and the nonlinear motion coupling only influence the amplitude of resonance spectral peak. In addition, factors influencing the nonlinear effects such as the vertical position and diameter of bracings and the pitch restoring coefficient are further investigated. It is revealed that the deviation of pitch resonance frequency has evident dependence on the ratio between nonlinear and linear volumetric variations, and an empirical formula estimating the resonance frequency is proposed using the observed dependence. Theoretically, both smaller bracing radius and larger pitch restoring coefficient are beneficial for suppressing the resonance induced by the nonlinear effects. The proposed model can be an effective tool for predicting the motion response, and the understanding of the resonance features is helpful for the design of semi-submersibles. Highlights: A mathematical model was proposed for a semi-submersible platform with bracings under irregular waves. The effects of bracings and nonlinear motion coupling on resonance were analysed. An empirical formula was proposed to approximate the variation of resonance frequency. Factors influencing the nonlinear effects were analysed.